Historical Ethnolinguistic Notes on Proto-Austroasiatic and Proto-Vietic Vocabulary in Vietnamese - Mark Alves (Journal of the Southeast Asian Linguistics Society, 2020)
This study provides updated numbers of and historical ethnolinguistic observations on Austroasiatic and Vietic etyma in Vietnamese. Lexical data from two dozen Vietic lects were assembled, half from the Mon-Khmer Etymological Database (MKED hereafter) and half from various other published and unpublished sources. Based on Ferlus’s preliminary reconstructions of Proto-Vietic (by Ferlus 2007 in the MKED), and data from Austroasiatic, Proto-Tai, and Old and Middle Chinese, approximately 800 items have been evaluated as viable reconstructions. However, of these, nearly 100 are Chinese loanwords of differing periods, and several are early Tai loanwords. The remaining nearly 700 items are native, including about 200 Proto-Austroasiatic etyma, with a few dozen local Austroasiatic words, and over 460 items specific to Vietic. Statistics have been gathered for cultural domains of the reconstructed vocabulary. A combination of etymological sources, semantic domains, and ethnohistorical data (i.e. archaeology, historical texts, and ethnographic information) allow for hypotheses about the ethnolinguistic circumstances of the early Vietic speech community and language contact situations. Many of the cultural domains are readily identified as part of a Neolithic lifestyle (i.e. words related to the natural environment, generic actions, etc.). Some, on the other hand, demonstrate social stratification (e.g. words related to economic practices) and developed agricultural practices (e.g. a large set of terms related to rice production). Others shed light on regional spread of cultural practices (e.g. betel-nut chewing and tooth-blackening) and intergroup contact (e.g. with Sinitic and Tai). Questions related to the spread of metallurgy and metal implements strongly support the influence of Chinese in metal terms and implements.